Spectrum and net counts rates of ambient low energy (0.2-10.0) MeV gamma rays in São Jose dos Campos in Brazil region - Malmonge Martin, Inacio (Seven Editora, 2023)
The measurement of the energy spectrum of environmental gamma radiation in the region of São José dos Campos, SP, Brazil, can indicate the radioactive chemical components existing in the land and air of this region. The portion of this radiation produced by primary and secondary cosmic rays are of lower intensities and vary very little with respect to time on the Earth's surface. Winds and rains also vary the intensity of this gamma radiation near the earth's surface through the exhalation of radon gas. Using a gamma radiation spectrometer calibrated between the lower limit of 180 keV and the upper limit of 10.0 MeV, it was possible to determine these counts as a function of measurement time in this region. DOI: 10.56238/pacfdnsv1-028